INTEGRATION OF LANDSAT AND SRTM DATA FOR PRELIMINARY EXPLORATION OF BAUXITE DEPOSITS, CASE STUDY: SOUTH EASTERN BINTAN ISLAND, RIAU ISLANDS PROVINCE (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
Bintan and surrounding islands are well known for the vast reserves of bauxite deposits in Indonesia. In Indonesia, Bauxite is generally formed through a laterization process of rocks such as granite, granodiorite, diorite, gabbro, and andesite which are rich in aluminosilicate minerals containing aluminum oxide (Al2O3). At this time with very high exploration costs, a minimal cost exploration support method is needed to find new potential reserves. Thus, remote sensing techniques can be effectively used as tools to identify the potential areas that contain bauxite deposits. This study presents the use of Landsat 7 and 8 imagery data from years 2000 and 2020, integrated with SRTM to analyze the spatial distribution of bauxite deposits around the Southern Bintan Islands. These data were processed and analyzed by the response of soil reflectance which may be similar to the mining/ex-bauxite mining area. The interpretation keys such as color, morphology, texture, and geological knowledge are used as a guidance of visual interpretation. The results of this study show that the region with bauxite potential has a slightly dark red color characteristic and a small partition of dark white in band 457 (Landsat 7) and 567 (Landsat 8). In addition, the morphology shows a gentle slope with a smooth to slightly rough texture. One of the small islands located in the southeast of Bintan Island, namely Poto Island, has these characteristics. Thus, it can be concluded temporarily that Poto Island has bauxite potential until the detailed mapping is carried out in further research.
Keywords: Bauxite; remote sensing; Southeastern Bintan Island; Poto Island